EGGA 3.0 - mastering English grammar through self-directed mobile learning - Abdul Talip, Abdul Hadi; Metom, Lilly; Ibrahim, Sueb; Noyan, John Francis; Bohari, Zubaidah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
EGGA 3.0 (English Grammar Guide App 3.0) is an upgraded and improved version of the innovative mobile application for learning English grammar. This self-directed mobile learning app is developed as a tool to help learners master fundamental English grammar concepts independently. The application provides structured learning materials, focusing on five grammar categories: Parts of Speech in English, Tenses, Subject-Verb Agreement, WH-Questions, and Modals, which are organised on a digital bookshelf. Each category has clear and detailed notes with simple examples to make learning easier. After reading the learning material, learners can test their understanding by taking quizzes with multiple-choice questions. These quizzes do not have a time limit, but responses have to be entered in sequence, and only one attempt per question is allowed. The learners will receive an instant report with their score and grade once the quiz is completed. EGGA 3.0 enhances learning by fostering autonomy, providing instant feedback to the learners, and stimulating their interest through interactive material. As such, grammar becomes easy, fun, and effective for mobile device learners. This method helps students connect with the information in a meaningful way and pushes them to keep working on the grammar exercises. EGGA 3.0 offers a fun and personalised way to learn English grammar skills. This mobile app provides easy access to language resources, allowing learners to practise anywhere. In addition to classroom teaching, EGGA 3.0 offers a more casual way to learn language, which makes it more fun and useful for students. It leverages mobile technology to enhance engagement and accessibility in language learning. Based on the learners’ feedback, the high mean scores showed that the users were satisfied with EGGA 3.0’s overall multimedia elements, namely, its graphics, sound, textual content, interface, and usefulness. EGGA 3.0 was able to attract the learners’ attention, and they displayed a desire to know more about the grammar learning app. Therefore, employing EGGA 3.0 for grammar learning may inspire students to develop and acquire their grammar abilities, offer a pleasant and dynamic learning environment for them, and give them a way to measure their own degree of grammatical knowledge.